1999
DOI: 10.1097/00000539-199912000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Ropivacaine 2 mg/mL, 5 mg/mL, or 7.5 mg/mL After Ilioinguinal Blockade for Inguinal Hernia Repair in Adults

Abstract: Ropivacaine, a new local anesthetic, proved to be effective for pain relief after hernia repair in ilioinguinal blocks accompanying general anesthesia. Plasma concentrations peaked after 30-45 min, and were within safe limits after application of 0.25 mL/kg of 2, 5, or 7.5 mg/mL ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Similarly Wulf et al reported consistent sensory blockade with all examined dosing schemes of ropivacaine but motor blockade only at higher dosages, implying use of the least amount and lowest concentration of local anaesthetic possible, to minimise TFNP incidence [17]. To date, there is insufficient evidence to support any particular local anaesthetic, and the ideal combination and dosage have yet to be determined [9, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Wulf et al reported consistent sensory blockade with all examined dosing schemes of ropivacaine but motor blockade only at higher dosages, implying use of the least amount and lowest concentration of local anaesthetic possible, to minimise TFNP incidence [17]. To date, there is insufficient evidence to support any particular local anaesthetic, and the ideal combination and dosage have yet to be determined [9, 18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition the technique is safe since several studies have demonstrated that the plasma concentration of ropivacaine remains below the toxic threshold provided the dose is limited to less than 300 mg [15, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the peak blood concentration is proportional to the dose injected and the concentration of the solution used, as has shown Wulf et al in 1999 in his study on ilio-inguinal nerve block using different concentration of ropivacaine: 0.2%, 0.5%, or 0.75% in hernia repair surgery [22]. …”
Section: Discussionmentioning
confidence: 99%
“…After brachial plexus block (190 mg ropivacaine with adrenaline), a mean concentration of 1.6 mg l ª1 and the highest individual concentration of 2.9 mg l ª1 have been measured without any adverse reactions suggesting cardiovascular or CNS toxicity (Hickey et al 1990). After ilioinguinal-iliohypogastric block, a mean ropivacaine concentration of 1.6 mg l ª1 and the highest individual concentration of 3.6 mg l ª1 have been reported without adverse reactions (Wulf et al 1999). However, signs of CNS toxicity could have gone unnoticed because in most cases patients were under general anaesthesia at the time of peak plasma concentrations.…”
Section: Clarithromy-mentioning
confidence: 98%